ECONOMIC VALUATION OF MANGROVE BIOLOGICAL SYSTEM ADMINISTRATIONS IN UJUNG PANGKAH AREA OF GRESIK, EAST JAVA - Friza Rahmawanto Wibowo; Gatot Yulianto; Benny Osta Nababan (SEAN Institute, 2023)
The mangrove ecosystem is important to the people of the Ujung Pangkah Subdistrict because they use it to catch fish, crabs, and shellfish and as a place to make mangrove wood. As a result, it is critical to ensure the long-term viability ecosystem of mangrove in a number, one of which is by providing economic reports on these ecosystems. The motivation behind this study is to gauge the monetary worth of mangrove biological systems. This study was led in Ujung Pangkah Locale utilizing an overview technique. The economic value of mangrove ecosystem services, which include support, supply, regulatory, and cultural services, is used to analyze the data. The outcomes show that the absolute financial worth of mangrove environment administrations covering an area of 1,445 Ha is Rp. 8.981.001.176.087/year or Rp. 6.215.225.727/Ha/year, which includes a value of Rp for supporting services. 7.967.215.987.975/year, the benefit of offering types of assistance is Rp. IDR 23.801.226.560 annually, 988.562.461.194 annually for regulatory services, and 1.421.500.358 annually for cultural services. Mangrove ecosystems have a high environmental service value and must be conserved in order to maintain their high economic value, as evidenced the highest value of economic is regulatory and supporting service. The results of this study's maps can provide local managers and decision-makers with a picture of what occurred to the target ecosystems' quality, enabling them to implement more effective management strategies for the conservation of these ecosystems.